The landscape of decent work in Peru during the period 2010 to 2016 - Quispe Quezada, Uriel Rigoberto (2019)
In this article, a descriptive review on decent work in Peru has been carried out with the intention of formulating an overview of the situational status of this type of employment and establishing what aspects are limiting its progress and development in the country. The research has been developed through the bibliographic search of academic articles, reports of competent authorities on the subject and the analysis of the statistics of some socioeconomic indicators related to decent work mainly from the period 2010 to 2016. The results obtained as a result of the research indicate that there is a significant deficit of decent work at national and regional level that affects an important percentage of the employed population in Peru because of the high levels of informality and poverty present in our economy. This shows that there is an urgent need to orient State policies to improve working conditions and education of the population in the country.